مدى الوعي والاهتمام بانماط التغذية في مجتمع السباحة - بوعبد الله, بن عبالله; طاهري, محمدامين (Institut d'Éducation Physique et Sportive - Mostaganem 2023/2024, 2024)
تهدف هذه الدراسة إلى معرفة مدى وعي واهتمام السباحين بأنماط التغذية المختلفة عبر مراحل الموسم الرياضي. لتحقيق هذا الهدف افترضنا أن السباحين يهتمون بأنماط التغذية خلال مرحلة التدريب، ومرحلة المنافسة، ومرحلة الراحة الإيجابية. و تم استخدام المنهج الوصفي حيث تم جمع البيانات بطريقة حديثة وفعالة، باستخدم رمز QR code لتمثيل الاستبيان عبر عينة تضم 60 سباحًا. من الذكور والإناث، فكانت الأغلبية من الذكور، وذلك لاختيار العينة بطريقة صدفية لضمان التمثيل العادل وتوفير الوقت. و بعد المعالجة الإحصائية أظهرت النتائج أن مستوى الوعي والاهتمام الغذائي لدى السباحين في جميع مراحل الموسم يُعتبر متوسطًا بناءً على هذا توصي الدراسة بدمج مبادئ التغذية السليمة كجزء أساسي من برامج التدريب اليومي. كما تُوصي بتخصيص جلسات استشارية فردية للسباحين مع أخصائيي التغذية لتحديد الاحتياجات الغذائية. // // // // // This study aims to assess the awareness and interest of swimmers in various nutritional patterns throughout the season. To achieve this goal, it was assumed that swimmers are concerned with nutritional patterns during training, competition, and positive rest phases. The descriptive approach was utilized, and data were collected efficiently using QR code representation for the questionnaire among a sample of 60 swimmers, consisting of both males and females, with the majority being males. This random sampling ensured fair representation and saved time. After statistical analysis, the results indicated that the level of nutritional awareness and interest among swimmers in all stages of the season is moderate. Based on these findings, the study recommends integrating proper nutritional principles as a fundamental part of daily training programs. Furthermore, it suggests allocating individual counseling sessions for swimmers with nutrition specialists to determine their dietary needs.
LES-2024-35
Keywords: السباحة - التغذية - االموسم الرياضي- الوعي الغذائي // // Swimming - Nutrition - Sports Season - Nutritional Awareness